(untitled) (Journal of Educational Sciences, 2019)
This article presents a historical and pedagogical analysis of the pedagogical component in professional military education. The authors have studied historical, memoir sources on the topic of the research, broadly studied the question of the military organization among nomads. The analysis of the formation of military pedagogical ideas until the end of the 18th century is carried out in the context of the development of military art, and the author made an analysis of training and military educational process among nomads. Since these issues played a significant role in the development of military formations and military organization, the authors could identify certain trends and the historical path development of pedagogical ideas in the system of military education. The characteristic features of training for the first period of development of military pedagogical ideas in the framework of military art (until the end of the XVIII century) are revealed. This is the formation of knowledge and skills on the basis of practice, drill training from childhood, training of future soldiers, battle cry that raised the spirit, unity, a personal example, etc.